2016
DOI: 10.17221/8678-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii in samples from cattle herds and sheep flocks in the Kars region of Turkey

Abstract: This study was aimed at determining the presence of C. burnetii in cattle and sheep herds in the Kars region of Turkey using serological and molecular methods. As a serological technique, C.burnetii IgG in blood sera and milk samples were investigated with ELISA. The results of these examinations revealed that 108 (43.2%) out of 250 sheep blood serum samples and 52 (14.85%) out of 350 cattle blood serum samples were seropositive for C. burnetii antibodies by ELISA. Out of 350 cattle and 250 sheep milk samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…These differences might stem from different climates, geographic location, sample size, year, species screened, and the cut-off value. 20,25 Previous studies 17,18,23 carried out in different provinces in eastern Anatolian region of Turkey showed that there has been an increase up to 14.8% in Q fever seroprevalence in cattle herds during the last decade. This increase may continue according to our result (19.4%) in the same region as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences might stem from different climates, geographic location, sample size, year, species screened, and the cut-off value. 20,25 Previous studies 17,18,23 carried out in different provinces in eastern Anatolian region of Turkey showed that there has been an increase up to 14.8% in Q fever seroprevalence in cattle herds during the last decade. This increase may continue according to our result (19.4%) in the same region as well.…”
Section: Discussionmentioning
confidence: 99%
“…3 In the last two decades, several epidemiological studies on Q fever have been conducted in ruminant herds in Turkey. [20][21][22][23][25][26][27] Detection of specific antibodies is a useful indication of recent infections and previous exposure. ELISA is recommended to detect these disease indications as a practicable and highly sensitive test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, 6% (n=4) of 66 sheep's milk and 0.6% (n=2) of 328 vaginal swabs from goats yielded C. burnetii DNA. In a study performed in Turkey, out of the 350 bovine milk samples and 250 ovine milk samples collected, 1,42% and 0,4% were found to be positive using the PCR technique, respectively 24 . The amplification of transposase gene (IS1111)…”
Section: Discussionmentioning
confidence: 99%
“…https://doi.org/10.17221/87/2022-VETMED Erzurum is an eastern city of Turkiye where livestock exchange occurs frequently and animal husbandry is intensive. Although molecular prevalence rates of C. burnetii in sheep and cattle have been reported from many regions in Turkiye (Can et al 2015;Gulmez Saglam and Sahin 2016), to the best of our knowledge, there is limited data on the molecular prevalence of C. burnetii in the BTM in Turkiye (Can et al 2015).…”
mentioning
confidence: 97%